Plant Litter Type Dictates Microbial Communities Responsible for Greenhouse Gas Production in Amended Lake Sediments - Yakimovich, Kurt M.; Emilson, Erik J. S.; Carson, Michael A.; Tanentzap, Andrew J.; Basiliko, Nathan; Mykytczuk, Nadia C. S. (Frontiers in Microbiology, 2018)
The microbial communities of lake sediments play key roles in carbon cycling, linking lakes to their surrounding landscapes and to the global climate system as incubators of terrestrial organic matter and emitters of greenhouse gases, respectively. Here, we amended lake sediments with three different plant leaf litters: a coniferous forest mix, deciduous forest mix, cattails (Typha latifolia) and then examined the bacterial, fungal and methanogen community profiles and abundances. Polyphenol were found to correlate with changes in the bacterial, methanogen, and fungal communities; most notably dominance of fungi over bacteria as polyphenol levels increased with higher abundance of the white rot fungi Phlebia spp. Additionally, we saw a shift in the dominant orders of fermentative bacteria with increasing polyphenol levels, and differences in the dominant methanogen groups, with high CH4 production being more strongly associated with generalist groups of methanogens found at lower polyphenol levels. Our present study provides insights into, and basis for future study on how shifting upland and wetland plant communities may influence anaerobic microbial communities and processes in lake sediments, and may alter the fate of terrestrial carbon entering inland waters.